ROLE OF BACTERIAL ESTERASE ON MERCURY DYNAMICS IN MANGROVE SEDIMENTS - Lopes, Paulo Roberto Salgado; Bispo, Maria das Graças Silveira; Crapez, Miriam Araújo Carlos; Wasserman, Julio Cesar (Geochimica Brasiliensis, 2019)
Tropical estuarine areas present microbial and geochemical conditions that have been pointed out as important conditions to trigger the mechanisms of mercury methylation improving its bioavailability to higher trophic levels. Despite the potential risk of these mechanisms to human health, few studies have reported in situ analysis in costal subtropical ecosystems, relating bacterial activity and mercury concentrations. In the present work we analyse the relationship between some relevant environmental parameters that may stimulate the bacterial activity and control mercury concentrations in the sediments of a tropical mangrove tidal flat. Forty-four samples were collected and analysed for total organic carbon, bacterial organic carbon, lipids, proteins, esterase activity and mercury concentrations and SEM/AVS. The redox potential, temperature and pH were also measured in situ. The results showed intense bacterial activity and increasing mercury levels when compared with local backgrounds. The use of SEM/AVS indicator recommended by USEPA as a criterium to check the sediment quality, did not show enough accuracy to predict the ecological bioavailability risk in sediments with high organic matter content. This methodology requires new approach to help decision making.